A linkage measure framework for the real estate sector - Song, Yu; Liu, Chunlu; Langston, Craig (International Journal of Strategic Property Management, 2010)
Linkage is one of the most important factors for gaining competitive advantage. Information on linkages is essential to understanding the structure of an economy, which is in turn important in formulating industry policies and business strategies. The hypothetical extraction method is used to measure the linkages by extracting a sector hypothetically from an economic system in the literature. In the previous research, however, the internal linkage (linkage within a sector) and sectoral linkages (linkage between two specific sectors) are ignored, and there is not a comprehensive framework to measure the linkages of a specific sector. Using the recently published Organisation for Economic Co‐operation and Development input‐output database at constant prices, this paper aims to resolve these two shortcomings and thereby propose a linkage measure framework to explore the linkages between the real estate sector and other sectors from a new angle. The relative and absolute linkages are termed and the total, backward, forward, internal and sectoral linkage indicators are formulated to investigate the linkages of the real estate sector from all directions. Empirical results show an increasing trend of these linkages, which confirms the increasing role of the real estate sector with economic maturity over the examined period. This framework also can be employed in other sectors. First Published online: 18 Oct 2010